GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG TABLET FE DI KELURAHAN SOKANEGARA KECAMATAN PURWOKERTO TIMUR KABUPATEN BANYUMAS TAHUN 2014 - Tin Utami (Universitas Harapan Bangsa Purwokerto, 2015)
The prevalence of anemia in Indonesia reached 50.9% and anemia in pregnancyprevelensia in Central Java stood at 57.7%. Iron deficiency anemia in pregnantwomen can lead to harmful effects for both mother and fetus. Precautions againstanemia by consuming Fe tablet routinely and regularly. The purpose of this studyto determine the level of knowledge about the tablet Fe pregnant women inKelurahan Sokanegara Kecamatan Purwokerto Timur Banyumas in 2014. This research method is quantitative descriptive cross-sectional approach,instrument used was a questionnaire given to 57 respondents using purposivesampling technique that will be analyzed by univariate analysis.The results showed that most respondents had a good knowledge of 30respondents (52.6%).It is concluded that the description of the level of knowledge about the tablet Fepregnant women in Sub Sokanegara Eastern District of Purwokerto, Banyumasregency in 2014 was good. Keywords: Knowledge, Tablet Fe, Pregnancy